A Cytotoxic Activity of Tahongai (Kleinhovia hospita Linn.) Leaves Extracts Using Brine Shrimp Lethality Test - Solihah, Indah; Herlina, Herlina; Rasyid, Riana Sari Puspita; Suciati, Tri; Khairunnisa, Khairunnisa (Science and Technology Indonesia, 2019)
Tahongai (Kleinhovia hospita Linn.) leaves had been known contain alkaloids, flavonoids, saponins, steroids, and tannins. At Komering, South Sumatera tribe, tahongai leaves had been known to treat tumor, cancer, polyps, acne, and dysmenorrhea. The study of cytotoxic activity of tahongai bark and stem were done. This study aims to determine the cytotoxic activity of tahongai leaves extracts using BSLT method. Tahongai leaves were extracted using gradual maceration with n-hexane, ethyl acetate, and ethanol 96%. Each extract was tested cytotoxic activity towards Artemia salina L. larvae. The yield of n-hexane, ethyl acetate, and ethanol extracts are 2,686%, 7,033%, and 7,933% respectively. Ethanol extract of tahongai leaves had the best cytotoxic activity with lethality value 76,667% at 500ppm. Statistical analysis with two way ANOVA showed extract and concentration had a significant (p<0,05) effect on larvae lethality percentage.